GIRLS' EDUCATION POLICY IN SUDAN: CHALLENGES AND PROSPECTS - Saifaldin Idris Onia (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2021)
Girls' education in the 21st Century, is not only a women's issue it is a development issue. Girls' education is `positively correlated with increased economic productivity, more robust labor markets, higher earnings, and improved societal health and well-being. Nevertheless, Sudan has witnessed low development of girls' education because of the country's traditions. Parents tended to look upon girls' education with suspicion, if not fear, that it would corrupt the morals of their daughters. Moreover, preference was given to sons, who, by education, could advance in society to the pride and profit of their family. Therefore, this study aimed to assess girls' education policy in Sudan. In doing so, this study followed a descriptive qualitative approach to the type of library research in which the data collection technique was carried out based on literature data. The study confirmed that there are several barriers to girls' education in Sudan including economic factors (i.e. cost of educational materials, girls are needed at home to contribute to the household economy), cultural factors (early marriages, tradition, and customs), and school factors (motivation as the lack of female role models). The researcher suggests that the authorities should enforce laws against the marriage of young girls. In addition, schools should be built in such a way that they are close to villages, allowing girls to attend. Furthermore, the nomads should be given lectures to be aware of the necessity of girls' education